2007
DOI: 10.1063/1.2720455
|View full text |Cite
|
Sign up to set email alerts
|

The FLUKA code: description and benchmarking

Abstract: The physics model implemented inside the FLUKA code are briefly described, with emphasis on hadronic interactions. Examples of the capabilities of the code are presented including basic (thin target) and complex benchmarks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
752
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,046 publications
(762 citation statements)
references
References 26 publications
6
752
0
4
Order By: Relevance
“…The production of cosmogenic neutrons and radioisotopes in Borexino was studied by using the Geant4 [17,18] and Fluka [19,20] simulation packages which are both commonly used to simulate deep underground, low background experiments. Their predictions are compared with our experimental data.…”
Section: Monte Carlo Simulations Of Cosmogenic Neutrons and Radioisotmentioning
confidence: 99%
“…The production of cosmogenic neutrons and radioisotopes in Borexino was studied by using the Geant4 [17,18] and Fluka [19,20] simulation packages which are both commonly used to simulate deep underground, low background experiments. Their predictions are compared with our experimental data.…”
Section: Monte Carlo Simulations Of Cosmogenic Neutrons and Radioisotmentioning
confidence: 99%
“…Particle fluxes originating from these operational beam losses were calculated with the MARS15 [66] code (later also with FLUKA [67]) and presented at the entrance to the ATLAS and CMS experimental halls (about 22 m from IP). It is found that background rates in detector subsystems strongly depend on the origin of MIB, particle energy and type.…”
Section: Beam Background Simulationsmentioning
confidence: 99%
“…Computations of particle production by both MARS and FLUKA [215,216,218] have been performed. Summaries of some simulations comparing results from different codes and lattices are shown in figure 34.…”
Section: Particle Production Simulationsmentioning
confidence: 99%
“…As a result of this calculation, a requirement for the proton-beam emittance was determined (see table V). Comparisons were made between MARS [210-214] (version 1507 is used throughout this document) and FLUKA [215,216] simulations for this target system [217].…”
Section: Progress Within the Ids-nf Accelerator Study To Datementioning
confidence: 99%